How Culture Transforms Government Aid: Evidence From Sumbawa Regency, Indonesia - Permata Cita, Fitriah; Zuhroh, Diana; Harsono (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2025)
This study investigates how government assistance, family income, and local culture jointly influence economic welfare in Sumbawa Regency, Indonesia. Moving beyond “isolated variable” analysis, this study develops an integrated framework to address policy gaps where social protection outcomes often fall short despite major investments. It extends “welfare state theory” by incorporating cultural dimensions that are typically overlooked in conventional economic models. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS), data were gathered from 201 randomly selected respondents among government aid recipients. Results show significant positive effects: government assistance (β = 0.342, p < 0.01), family income (β = 0.458, p < 0.001), and local culture (β = 0.231, p < 0.05). The model demonstrates strong explanatory power (R² = 0.687) and predictive relevance (Q² = 0.524). Findings reveal that family income remains the strongest welfare determinant, while effective government aid requires proper targeting and allocation. Significantly, local practices like gotong royong (mutual assistance) strengthen social cohesion, validating culture's role as an active economic determinant. This study contributes to Islamic economics literature by demonstrating how local cultural practices aligned with Islamic principles of ta'āwun (cooperation) and maslahah (public interest) enhance welfare outcomes in Muslim-majority contexts where Islamic values shape economic behavior. The research proposes practical recommendations for “culturally-sensitive” assistance programs that integrate Islamic social finance instruments (zakat and waqf) with income enhancement strategies and cultural capital development. its also emphasizes establishing monitoring systems that track both welfare indicators and cultural sustainability. These findings offer replicable frameworks for welfare policy design in developing countries where cultural and religious dimensions fundamentally influence development outcomes.